The Effect of The Example Non-Example Learning Model Assisted by Infographic Media on The Persuasive Text Writing Skills of Eighth Grade Students at SMP Negeri 6 Percut Sei Tuan - Agnes Endwitri Sihombing; Yuhdi, Achmad (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This study aims to analyze the effect of the example non-example learning model assisted by infographic media on the persuasive text writing skills of eighth-grade students at SMP Negeri 6 Percut Sei Tuan. This research employs a quasi-experimental method with a two-group post-test only control design. The data collection technique used in this study is a test in the form of a post-test assignment for writing persuasive texts. To analyze the persuasive text writing skills, the data were analyzed by conducting two prerequisite tests: 1) Normality Test; 2) Homogeneity Test. After conducting the normality and homogeneity tests, the data were analyzed using hypothesis testing. The research results indicate that 1) The persuasive text writing skills of eighth-grade students at SMP Negeri 6 Percut Sei Tuan using the conventional learning model are categorized as fair, with an average score of 63.38; 2) The persuasive text writing skills of eighth-grade students at SMP Negeri 6 Percut Sei Tuan using the Example Non-Example learning model assisted by infographic media are categorized as good, with an average score of 84.03. These findings indicate that the Example Non-Example learning model assisted by infographic media is more effective in improving persuasive text writing skills. Based on the t-test, with a significance level of α = 0.05 and n = 31, the obtained t-table value is 2.04 and the calculated t-value is 6.162. Since the calculated t-value is greater than the t-table value (6.162 > 2.04), the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This proves that the Example Non-Example learning model assisted by infographic media has a significant effect on the persuasive text writing skills of eighth-grade students at SMP Negeri 6 Percut Sei Tuan.